The Urgency of Regulating the Results of Absorption of Constituent Aspirations The Regional House of Representatives for Preparation Budget Regional Income and Expenditure - Minto, Totok Minto Leksono; Suhartono, Slamet; Hufron; Hadi, Syofyan (Technium Social Sciences Journal, 2022)
This study examines and identifies the need to regulate the results of the absorption of constituent aspirations by the regional people’s representative council to be included in the preparation of the regional budget for regional income and expenditures in order to realize prosperity. This study uses a normative legal research method which entirely uses secondary data. The study found the need to regulate the results of the absorption of the aspirations of the members of the Regional People’s Representative Council to be urgent for the preparation of regional revenue and expenditure budgets, among others; 1) as an effort to welfare the people, through the functions given with the principle of exemplary which is very important in carrying out the mandate of the people as well as possible, 2) In the preparation of budget regional income and expenditure budget function is an important function as a legislative institution that has the authority to determine budget allocations needed by constituents through recess by absorbing and collecting constituent aspirations, 3) Process and schedule for preparing budget regional income and expenditure already listed in Permendagri No. 13/2006, as well as budget allocation in accordance with Minister of Home Affairs Regulation No. 21/2011 and Permendagri No.33/2017. Determination of policies regarding the budget is the authority of the executive, but in a further process, namely the determination of allocations and their ratification is the responsibility of the executive, The legislature has legislative powers. Thus, the executive and legislative bodies cooperate with each other in the budget preparation process